Reassessment of clinical implication of pretransplant surgical procedures for pulmonary invasive fungal lesions. Issue 1 (29th November 2018) - Shingai, Naoki; Kaito, Satoshi; Yamada, Yuta; Konishi, Tatsuya; Nagata, Akihito; Kurosawa, Shuhei; Watakabe‐Inamoto, Kyoko; Igarashi, Aiko; Najima, Yuho; Muto, Hideharu; Kobayashi, Takeshi; Doki, Noriko; et al.
Abstract: Dealing with the recent series of allogeneic hematopoietic stem cell transplantation (allo‐SCT) performed this decade, we reassessed the clinical impact of pretransplant surgical procedures (SP) for pulmonary lesions of invasive fungal disease (IFD) on subsequent transplant outcome. We focused on the clinical outcomes of seven patients with pulmonary IFD who underwent segmentectomy (n = 4), lobectomy (n = 2) or abscess incision with drainage only (n = 1), and compared results to those of 21 patients carrying pulmonary IFD who never underwent invasive SP before allo‐SCT. The rate of exacerbation of pulmonary lesions by 180 days after allo‐SCT did not differ significantly between groups (32.2% vs 42.9%, P = 0.69). Moreover, no significant differences in non‐relapse mortality (46.4% vs 42.3%, P = 0.93) or overall survival (53.6% vs 30.9%, P = 0.45) at 1 year were evident between groups. These results indicate that pretransplant SP for pulmonary lesions might have no survival benefit under the current antifungal prophylaxis or treatment modality.